The concept of Narcissistic Personality Disorder–Three levels of analysis for interdisciplinary integration - Jacobs, Kerrin A. (Frontiers in Psychiatry, 2022)
In this paper, I distinguish three different levels for describing, and three corresponding ways for understanding, deficient empathy as the core of NPD. On the macro level, deficient empathy can be explained as disturbed interpersonal functioning, and can be understood as lack of recognition. On the meso-level, deficient empathy can be described as psychic disintegration, and can be understood specifically in its dissocial aspects. Psychic disintegration in NPD correlates with somatic changes, i.e., dysfunctional affective empathy and mind-reading on the micro level of description, which is the third level. The “core-deficit-model of NPD” that I outline, while not rejecting reductionist approaches outright, argues in favor of integrating (top-down/bottom-up) various functionalist descriptions of empathy into a wider conceptual framework of bio-psycho-social functioning. The “core-deficit-model of NPD” is interdisciplinary, can bypass monodisciplinary skepticism, and removes purported barriers between explaining and understanding the "lack" of empathy as the core of pathological narcissism.